Akad Musaqah pada Praktik Matteseng dalam Meningkatkan Kesejahteraan Masyarakat di Kecamatan Pitumpanua Kabupaten Wajo - Lestari, Widia; Anwar, Nurfiah; Katman, Muhammad Nasri (Pendidikan Agama Islam STIT Palapa Nusantara, 2024)
The practice of matteseng is a form of work carried out by the community in Pitumpanua sub-district, Wajo Regency, which is established between land owners and managers. It is necessary to study whether the practice of matteseng by implementing musaqah contracts can improve community welfare. The method used in this study is qualitative method using phenomenological research approach. The data sources used are primary data (direct information) and secondary data (books, journals and related articles). The data is obtained through interviews, documentation, and observation. The results showed that the application of musaqah contract in matteseng practice has not been maximized enough and the improvement of community welfare when viewed the fulfillment of the 5 aspects of Sharia maqashid has not been fully fulfilled.